National identity construction through grammatical cohesive devices in independence day speeches in Ghana: A corpus-based study - Eric Antwi; Kwabena Sarfo Sarfo-Kantanka; Joseph Benjamin Archibald Afful (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
The construction of national identities in post-colonial nations is significantly influenced by political discourse, as political leaders use language to shape and reinforce a sense of collective identity. In this context, Ghana provides a compelling case for examining how grammatical cohesive devices in Independence Day Speeches contribute to national identity formation. This study employs a corpus-based approach, focusing on Ghana’s Independence Day speeches delivered by various presidents from 2010 to 2024, to capture trends across successive administrations. Drawing on Social Identity theory and Theory of Cohesion, this study examines how references to Ghana’s political past, present, and future contribute to the formation of a unified national identity. The findings indicate that demonstratives are the most dominant grammatical cohesive devices employed by Ghanaian presidents. These demonstratives mostly describe events, people and actions pertinent to the national narrative. One noteworthy finding is the use of the additive conjunction ‘and’, which serves a dual function: it links ideas linguistically while also creating contrast within discourse. This dual role enhances the effectiveness of the speeches. These findings highlight the crucial role of cohesive devices in reinforcing a shared national identity and fostering solidarity among the populace.